Effect of Boiling Treatment on Linoleic Acid-Induced Oxidation of Myofibrillar Protein in Grass Carp - Mengcong Liu; Fuhua Li; Yuan Tang; Jichun Zhao; Xiaojuan Lei; Jian Ming (Foods)
The aim of this study was to investigate the promotion of linoleic acid (OLA)-induced myofibrillar protein (MP) oxidation by boiling treatment. The effect of the boiling treatment on grass carp MP oxidation induced by OLA was investigated. The total sulfhydryl content, fluorescence intensity, and amino acid content were reduced with the increasing OLA concentration after the boiling treatment, while the boiled oxidized MP’s carbonyl content (4.76 ± 0.14 nmol/mg) was 2.14 times higher than that of the native MP (2.22 ± 0.02 nmol/mg) at an OLA concentration of 10 mM. Additionally, the secondary structure of MP became more disordered, shifting from an α-helix to random coils and β-turns. When the concentration of OLA was higher than 5 mM, both the surface hydrophobicity and water holding capacity (WHC) decreased with the increasing OLA concentration. Furthermore, the boiling treatment led to a reduction in immobile water and an increase in free water content in the MP gel. These findings establish a theoretical basis for regulating MP oxidation to improve fish quality during boiling.